THE EFFECT OF CAREER DEVELOPMENT AND ORGANIZATIONAL COMMITMENT TO EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A MODERATING VARIABLE IN PT. P&P LEMBAH KARET - Andhika Putra, Rio; Mittra Candana, Dori; Lima Krisna, Nandan (Dinasti Publisher, 2020)
This study aims to determine how much influence the Career Development and Organizational Commitment on Employee Performance with Job Satisfaction as a Moderating Variable at PT. P&P Valley Karet. Methods of data collection through the distribution of questionnaires with a sample of 77 respondents PT. P&P Valley Karet. The analytical methods used are validity test, reliability test, classic assumption test, statistical test and MRA test. Based on the results of the study found that Career Development has a positive and significant effect on Employee Performance with a significant level (0.009 <0.05). Organizational Commitment has a positive and significant effect on Employee Performance with a significant level (0,000 <0.05). Career Development moderates the relationship of Job Satisfaction to Employee Performance with a significant level (0.041 <0.05). Organizational Commitment moderates the relationship of Job satisfaction with Employee Performance with a significant level (0,000 <0.05). Career Development Contribution and Organizational Commitment to Employee Performance is 58.4% while the remaining 41.6% is influenced by other variables outside this study. Finally, the authors suggest to the management of PT. P&P Lembah Karet that Employee Performance will improve if management enhances Career Development, Organizational Commitment and Job Satisfaction through its indicators.